MENCERMATI PERUBAHAN KURIKULUM PENGAJARAN BAHASA ARAB DI SEKOLAH - Dian Ekawati (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
The curiculum plays an important role in education. The curiculum determines the type and qualification of an educational institution that contains the plan for the implementation of education in the classroom, School, country, region or nation. Curiculum is applied within a certain period and then revised according to the demands of the era and the development of society. Programing Arabic language material from primary until university with a sufficient meeting is considered very important for learners to Know and understand the news or information an arabic. On the other hand curriculum changes are also needed if the curriculum that prevails at that time did not match the needs of the community in its time. The stages of curriculum development are the formulation of objectives, determining the content, selecting activities, evaluating. The Arabic language development paradigm in school is the dichotomous paradigm, mechanism and orgamism. The aspect of creating a religious atmosphere in schools / madrasah and college is the position of creating a religious atmosphere, the urgency of creating a religious atmosphere and operational by introducing Arabic education as one of the important capital in studying Islam. Arabic is not the language of Muslims, but Arabic is the language of the Qur'an.